Reciprocal cooperation between unrelated rats depends on cost to donor and benefit to recipient - Schneeberger, Karin (BioMed Central, 2012)
BACKGROUND: Although evolutionary models of cooperation build on the intuition that costs of the donor and benefits to the receiver are the most general fundamental parameters, it is largely unknown how they affect the decision of animals to cooperate with an unrelated social partner. Here we test experimentally whether costs to the donor and need of the receiver decide about the amount of help provided by unrelated rats in an iterated prisoner's dilemma game. RESULTS: Fourteen unrelated Norway rats were alternately presented to a cooperative or defective partner for whom they could provide food via a mechanical apparatus. Direct costs for this task and the need of the receiver were manipulated in two separate experiments. Rats provided more food to cooperative partners than to defectors (direct reciprocity). The propensity to discriminate between helpful and non-helpful social partners was contingent on costs: An experimentally increased resistance in one Newton steps to pull food for the social partner reduced the help provided to defectors more strongly than the help returned to cooperators. Furthermore, test rats provided more help to hungry receivers that were light or in poor condition, which might suggest empathy, whereas this relationship was inverse when experimental partners were satiated. CONCLUSIONS: In a prisoner's dilemma situation rats seem to take effect of own costs and potential benefits to a receiver when deciding about helping a social partner, which confirms the predictions of reciprocal cooperation. Thus, factors that had been believed to be largely confined to human social behaviour apparently influence the behaviour of other social animals as well, despite widespread scepticism. Therefore our results shed new light on the biological basis of reciprocity.